Analysis of Spelling Errors in Vocabulary Writing at Second Grade Students of MA Miftahul Ulum Bettet - Sholehah, Wardatus; Yuliawati, Fitrah; Setiyawan, Arisandi (Universitas PGRI Adi Buana Surabaya, 2025)
Spelling plays a crucial role in vocabulary mastery and writing accuracy, which are essential components of English language learning. However, many students persistently make spelling errors, particularly in vocabulary writing, due to limited understanding of English spelling conventions and inadequate instructional support. Although previous research has addressed common writing errors, specific attention to spelling errors in vocabulary remains insufficient. This study aims to identify the types of spelling errors and the contributing factors among second-year students at MA Miftahul Ulum Bettet, Pamekasan. Employing a qualitative research design with a case study approach, the researcher collected data through classroom observations, students’ writing assignments, and structured interviews. The data were analyzed using Corder’s (1974) error analysis model, which involves error identification, classification, explanation, and evaluation. The findings revealed four types of spelling errors: omission, addition, substitution, and transposition, with omission being the most frequent. Contributing factors identified include limited vocabulary knowledge, phonetic influence from the first language (L1), insufficient writing practice, and inadequate corrective feedback from teachers. The findings highlight that students tend to rely on phonetic spelling rather than correct orthographic forms. The study concludes that consistent writing practice, enhanced vocabulary input, and effective teacher feedback are essential for reducing spelling errors and improving students’ overall English writing competence.